Protection against protectionists: How FDI positions may mitigate transatlantic trade conflicts - Stefan Kooths; Galina Potjagailo (Institut für Weltwirtschaft (IfW), 2017)
The mercantilist attitude of the new U.S. presidency raises the fear of the United States turning towards a protectionist stance in trade relations with the European Union. The high bilateral trade surplus of the Europeans and Germany in particular feed into this concern. In 2015, the export surplus of the European Union amounted to 115 billion Euro (German share: 49 billion Euro).
Keywords: 330